Trapezius muscle activation levels and ratios during scapular retraction exercises: A comparative study between patients with subacromial impingement syndrome and healthy controls. (July 2019) - Kara, Dilara; Harput, Gulcan; Duzgun, Irem
Abstract: Background: Little is known about trapezius muscle activities during scapular retraction exercises in patients with subacromial impingement syndrome. The aim of this study was to compare upper trapezius, middle trapezius and lower trapezius muscle activity and upper/middle and upper/lower trapezius ratios between patients with subacromial impingement syndrome and healthy individuals during six scapular retraction exercises. Methods: Twenty-two patients with subacromial impingement syndrome and 22 healthy individuals participated. Upper, middle, and lower trapezius activities were measured by surface electromyography, while the participants performed six scapular retraction exercises at different shoulder abduction angles in a standing position. Upper/middle and upper/lower trapezius ratios were also calculated. Repeated-measures analyses of variance were performed to determine whether muscle activation levels and ratios differed between groups during exercises. Findings: There was no significant exercise × group interactions for upper, middle, and lower trapezius activation levels and upper/middle and upper/lower trapezius ratios ( P  > .05). A main effect for the exercise was observed for the upper/middle and upper/lower trapezius ratios ( P  < .05). Interpretation: Compared to healthy individuals, patients with subacromial impingement syndrome did not exhibit different upper, middle, and lower trapezius activity and had similar upper/middle and upper/lower trapezius ratios during the various scapular retraction exercises. Therefore, scapular retraction exercises with various shoulder abduction could be safely offered for the patients with subacromial impingement syndrome since it does not lead to abnormal compensatory trapezius muscle activity. If the goal is to minimize upper/middle and upper/lower trapezius ratios, the scapular retraction exercises at 0° shoulder abduction may be used in early stage of shoulder rehabilitation. Highlights: Patients have normal trapezius activity compared to healthy group during retraction exercises. Retraction exercises do not cause abnormal compensatory trapezius muscle activity. Retraction exercises can be safely used in shoulder impingement exercise programs.